2020
DOI: 10.3390/biomedicines8070180
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism by which Ergosterol Inhibits the Promotion of Bladder Carcinogenesis in Rats

Abstract: We previously showed that ergosterol has an inhibitory effect on bladder carcinogenesis. In this study, we aimed to elucidate the molecular mechanism by which ergosterol inhibits bladder carcinogenesis using a rat model of N-butyl-N-(4-hydroxybutyl)nitrosamine-induced bladder cancer. The messenger ribonucleic acid (mRNA) expression level of the cell cycle-related gene cyclin D1 and inflammation-related gene cyclooxygenase-2 in bladder epithelial cells was significantly increased in the carcinogenesis group com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…The mRNA expression level of cyclin D1 in bladder epithelial cells was significantly higher in the carcinogenesis group than in the control group. This result was consistent with previous reports using bladder cancer model rats [9]. In contrast, in rats treated with brassicasterol, the expression level of cyclin D1 was significantly decreased compared with that in the carcinogenesis group, which was almost the same as that in the control group.…”
Section: Effects Of Brassicasterol On the Mrna Expression Levels Of C...supporting
confidence: 92%
See 2 more Smart Citations
“…The mRNA expression level of cyclin D1 in bladder epithelial cells was significantly higher in the carcinogenesis group than in the control group. This result was consistent with previous reports using bladder cancer model rats [9]. In contrast, in rats treated with brassicasterol, the expression level of cyclin D1 was significantly decreased compared with that in the carcinogenesis group, which was almost the same as that in the control group.…”
Section: Effects Of Brassicasterol On the Mrna Expression Levels Of C...supporting
confidence: 92%
“…The results of this study clarified that brassicasterol suppresses bladder carcinogenesis by acting on cell cycle-related signaling, inflammation-related signaling, and androgen signaling via multiple mechanisms. These effects were similar to those of oral ergosterol administration to bladder cancer model rats [9]. Therefore, it is highly possible that the inhibitory effect of Choreito treatment on bladder carcinogenesis is due to the brassicasterol, which is a metabolite of ergosterol contained in Polyporus Sclerotium.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Ergosterol also alleviates the symptoms of LPS-induced acute lung injury in mice by downregulating COX-2 expression [ 58 ]. Another study also reported that ergosterol suppresses mRNA expression of COX-2 in rat bladders [ 59 ].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Ikarashi et al, starting from previously data that suggest an inhibitory effect byergosterol on bladder carcinogenesis, elucidated its molecular mechanism using a rat model of N-butyl-N-(4-hydroxybutyl)-nitrosamine-induced bladder cancer. They also analyzed various aspects of the cell cycle, inflammation-related signaling, and androgen signaling, suggesting that ergosterol inhibits bladder carcinogenesis [ 10 ]. Georgieva et al demonstrated that hemocyanins isolated from H. aspersa , H. lucorum, and R. venosa , as well as the mucus from H. aspersa exert an antitumor activity in vitro against colorectal carcinoma cell line HT-29, reducing cell viability with a mechanism that includes the induction of apoptosis [ 11 ].…”
mentioning
confidence: 99%